MEMUTUS RANTAI IMPUNITAS: PENYELESAIAN PELANGGARAN HAK ASASI MANUSIA YANG BERAT DALAM PERSPEKTIF KEADILAN TRANSISI - Mohammad Faisal Reza (2022)
Over the last few decades, countries around the world have experienced changes in political regimes. This is no exception in our country. The transition of power from the new order to reformation put Indonesia in a transitional period of legal politics. Efforts to enforce human rights violations in a country in transition are not easy. Because it is closely related to the tug of war between political and legal interests. In the midst of the change in legal politics, the transitional justice paradigm can answer the stagnation of cases of enforcement of gross human rights violations. This study uses a type of normative juridical research. The normative juridical research method with interviews is a research that refers to the legal norms contained in the legislation. The problem approach used in this legal research is the Legislative, case, and conceptual approach. The results of this study reveal that there are two main methods in the transitional justice paradigm, namely through the mechanism of criminal sanctions or the judicial route and mechanisms outside of criminal sanctions, namely reparations, reconciliation and compensation. This paper tries to answer the resolution of serious human rights violations through the paradigm of transitional justice and the ideal mechanism in resolving cases of serious human rights violations. Keywords: Human Rights Violations, Transitional Justice, Truth and Reconciliation Commission, Protection, Victims